Comparative study of secondary coniferous forests in the Biosphere Reserve Sierra de las Minas, Guatemala: with an emphasis on the impacts of forest management - Estrada Chinchilla, L.N. (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2005